Experiences and perceptions of trial participants and healthcare professionals in the UK Frozen Shoulder Trial (UK FROST): a nested qualitative study. Issue 6 (11th June 2021) - Srikesavan, Cynthia; Toye, Francine; Brealey, Stephen; Goodchild, Lorna; Northgraves, Matthew; Charalambous, Charalambos P; Rangan, Amar; Lamb, Sarah
Abstract : Objectives: To explore the experiences and perceptions of trial participants and healthcare professionals in the UK Frozen Shoulder Trial (UK FROST), a multicentre randomised controlled trial that compared manipulation under anaesthesia (MUA), arthroscopic capsular release (ACR) with a 12-week early structured physiotherapy programme (ESP) in people with unilateral frozen shoulder referred to secondary care. Design: Nested qualitative study with semistructured interviews. We used constant comparison method to develop our themes. Setting: This qualitative study was nested within the UK FROST. Participants: 44 trial participants (ESP: 14; MUA: 15; ACR: 15), and 8 surgeons and 8 physiotherapists who delivered the treatments in the trial. Results: Trial participants found UK FROST treatments acceptable and satisfactory in terms of content, delivery and treatment benefits. Participants in all arms experienced improvements in pain, shoulder movements, and function. Participants said they would choose the same treatment that they received in the trial. Surgeons and physiotherapists felt that the content and delivery of UK FROST treatments was not significantly different to their routine practice except for the additional number of physiotherapy sessions offered in the trial. They had mixed feelings about the effectiveness of UK FROST treatments. Both stressed the value of including hydrodilatation as a comparator of other treatment options. Physiotherapists raised concerns about the capacity to deliver the number of UK FROST physiotherapy sessions in routine clinical settings. Shared perceptions of trial participants, surgeons and physiotherapists were: (1) Pain relief and return of shoulder movements and function are important outcomes and (2) Adherence to exercises leads to better outcomes. Conclusion: In general, our findings indicated that trial participants, and surgeons and physiotherapists who delivered the treatments had positive experiences and perceptions in the UK FROST. Early qualitative investigations to explore the feasibility of delivering treatments in real-world settings are suggested in future trials in the frozen shoulder. Trial registration number: International Standard Randomised Controlled Trial Register, ID: ISRCTN48804508 . Registered on 25 July 2014; Results